The Dialectic Psychology perspectives - Oliveros M., Ricardo (2010)
The present paper exposes the dialectic psychology perspectives in the twentieth first century Peru. We ponder about the dialectics psychology denomination, connecting them to other denominations used in the materialist psychology trend. We analyze the relations between dialectics psychology and social neuroscience, delimiting both the psychological sciences field and the neuroscience field. We develop issues from the emancipator project of dialectics psychology, precising personal development and psychological orientation aspects. We propound new aspects of the revolutionary paradigm in the psychism and personality, formulating a research plan of the key issues in dialectics psychology.